Face cells encode object parts more than facial configuration of illusory faces - Sharma, Saloni; Vinken, Kasper; Jagadeesh, Akshay V.; Livingstone, Margaret S. (Nature communications, 2024)
Humans perceive illusory faces in everyday objects with a face-like configuration, an illusion known as face pareidolia. Face-selective regions in humans and monkeys, believed to underlie face perception, have been shown to respond to face pareidolia images. Here, we investigated whether pareidolia selectivity in macaque inferotemporal cortex is explained by the face-like configuration that drives the human perception of illusory faces. We found that face cells responded selectively to pareidolia images. This selectivity did not correlate with human faceness ratings and did not require the face-like configuration. Instead, it was driven primarily by the “eye” parts of the illusory face, which are simply object parts when viewed in isolation. In contrast, human perceptual pareidolia relied primarily on the global configuration and could not be explained by “eye” parts. Our results indicate that face-cells encode local, generic features of illusory faces, in misalignment with human visual perception, which requires holistic information. Macaque face cells respond to objects humans perceive as illusory faces, yet the specific features that drive these responses remain unclear. Here, the authors show face cells respond mostly to object parts, without needing the face-like configuration crucial for the human perceptual illusion.